Modulation of acetylcholinesterase activity using molecularly imprinted polymer nanoparticles. Issue 35 (31st March 2022) - Piletsky, Sergey A.; Bedwell, Thomas S.; Paoletti, Rachele; Karim, Kal; Canfarotta, Francesco; Norman, Rachel; Jones, Donald J. L.; Turner, Nicholas W.; Piletska, Elena V.
Abstract : Epitope mapping and nanoMIP development lead to materials that modulate enzyme activity and promote reactivation after antagonist exposure. Abstract : Modulation of enzyme activity allows for control over many biological pathways and while strategies for the pharmaceutical design of inhibitors are well established; methods for promoting activation, that is an increase in enzymatic activity, are not. Here we demonstrate an innovative epitope mapping technique using molecular imprinting to identify four surface epitopes of acetylcholinesterase (AChE). These identified epitopes were then used as targets for the synthesis of molecularly imprinted nanoparticles (nanoMIPs). The enzymatic activity of AChE was increased upon exposure to these nanoMIPs, with one particular identified epitope nanoMIP leading to an increase in activity of 47× compared to enzyme only. The impact of nanoMIPs on the inhibited enzyme is also explored, with AChE activity recovering from 11% (following exposure to an organophosphate) to 73% (following the addition of nanoMIPs). By stabilizing the conformation of the protein rather than targeting the active site, the allosteric nature of MIP-induced reactivation suggests a new way to promote enzyme activity, even under the presence of an inhibitor. This method of enzyme activation shows promise to treat enzyme deficiency diseases or in medical emergencies where an external agent affects protein function.